EFFECT OF AGROCHEMICALS ON THE GROWTH OF DIFFERENT TRICHODERMA ISOLATES - LAHARI KARUMURI; R. K. SINGH (The Bioscan, 2015)
In this study we aimed to assess the compatibility of heavily spraying insecticides, pesticides and herbicides in M. P. Region with Trichoderma strains by using Poison food technique. Four commonly used fungicides, four insecticides and four herbicides were tested at two different concentrations, 500 and 1000ppm. The growth of Trichoderma strains was mostly inhibited by the carboxin+thiram, thiophanate methyl, quizalofop ethyl and chlorpyriphos. While, Trichoderma strains could grow easily with the Pyraclostrbin+metiram, pyraclostrobin, butachlor, pendimethalin, imizathyper, malathion and dimethoate. A progressive increase in percent inhibition of radial growth in the fungus was observed as the concentrations of the agrochemical increased. The present results will help delineate the possibility of combining Trichoderma strains, biocontrol agents and agrochemicals for use in an integrated pest management approach.